Advancing Hybrid Vehicle Technology: A Systematic Review of Power Transmission Routes in Leading Hybrid Systems - Li, Jiajun (Transactions on Environment, Energy and Earth Sciences, 2024)
This paper provides a comprehensive analysis of power transmission routes in contemporary hybrid vehicles, focusing on the characteristics and technological innovations of leading hybrid systems. The study examines five representative models: Toyota’s Prius with THS (Toyota Hybrid System), Nissan’s Sylphy with e-POWER, Honda’s Accord featuring i-MMD (Intelligent Multi-Mode Drive), and BYD’s models equipped with DM-i (Dual Mode Intelligent), as well as Great Wall’s Harvard with Hi4 (Hybrid Intelligent 4WD) system. Through a systematic comparison of these hybrid powertrains, we identify key trends in hybrid vehicle technology development. Our analysis reveals a shift towards increased electrification, with motor-driven systems becoming more prevalent. We also observe a growing emphasis on optimizing engine efficiency and integrating advanced power-split mechanisms. The paper concludes by predicting future developments in hybrid power transmission, highlighting the potential for further improvements in fuel economy, performance, and emissions reduction. This research contributes valuable insights for automotive engineers, policymakers, and researchers involved in the advancement of hybrid vehicle technology.